CRIMES AGAINST CHILDREN AS ACTORS - Muhammad Chalil; Djauhari Djauhari (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The word "mandate" is quite broad sense, but depending on the logic of man who entrusted the mandate to him, Islam teaches its followers to have a conscience that is sensitive, with a view to preserving and maintaining the rights of Allah and charitable man of truthful as ever Rasulullah Saw said, which means: "You're all a leader and you all will be held accountable for what he said about your leadership, ............., male (husband) is a leader in a family environment, and he will be asked about what he styles , women (wives) also leader in controlling her household, ........ "(HR.Bukhari) The hadith explains that the liability which carry on the shoulders of every Muslim both the husband and wife in this world, no one from any private, small or large, but it must be responsible for the mandate that has been carry and hold it well, for example to all children before growing up in essence is the right of children rests with the parents (father / mother), if the neglect of children's rights means committing a crime at the same time ignoring the mandate and responsibilities in answer to the Lord and make mistakes against themselves with the attitude and relinquish control over their power, this has resulted in an unruly child and certainly hard to be directed to the right path. The main task as parents is to nurture a personality strong to children, introducing his Lord, and instill that success in life both materially and spiritually is in accordance with the ideals of pure wholeheartedly, then he has done something useful for him, family, and the environment; In addition, as one of the children as human resources and the future generation, it should get special attention from the government, in order to develop the child to achieve a strong human resources and quality. Associated with child development necessary legal infrastructure to anticipate all the problems that arise, relating to the interests of the child as well as concerning irregularities attitudes and behaviors that make children forced held for trial. For example, on one of the main mental children who are still in the stage of self, sometimes easily influenced by the circumstances surrounding environment. So if the environment in which the child is bad, can be affected soul on actions that may violate the law, it can be detrimental to himself and the community environment, not least the action is to drag them to deal with law enforcement officers. In the family, children are part of society, has the same rights that must be protected and respected, even every country where compulsory care as well as adequate protection of the rights of children, including civil rights, economic, social and cultural benefits, it looks like the position and rights of children when seen from a juridical perspective has not been seriously considered by the government, law enforcement and the community at large and still far from what actually should be given to them. Special on Child Rights is part of the human rights and protection guaranteed by international law and national law, which universal has protected in the Universal Declaration of Human Rights (UDHR) and the International on Civil and Political Rights (ICPR). Differences of treatment on children's rights with adults, set in a special international conventions. As stated in the Declaration of the Rights of the Child: "... the child, by reasons of his physical and mental immaturity, needs special safeguards and care, Including Appropriate legal protection, before as well as after birth ..." The Vienna Declaration of 1993 generated by the World Conference of Human Rights Human Rights (HAM), re-emphasized the principle of "First Call for children", which emphasizes the importance of national efforts and international levels to promote the rights of the child to "survival protection, development and participation." While the concept of child protection in Indonesia has made the rules, essentially upholds and attention to the rights of children, namely after the ratification of the Convention on the Rights of the Child (CRC) include: Law No. 39 of 1999 on Human Rights; Law Number 11 Year 2012 on Child Criminal Justice System; Act No. 35 of 2014 on the Amendment of Act No. 23 of 2001 on the Protection of Children; So that the state and society have a duty to protect against the growth of the child, both physically, psychology, social, economic and political, as for any form of protection is emphasized on children in vulnerable conditions of discrimination, exploitation and violence, such as children with disabilities special, abandoned children, children who grow up in poor families and children who are in orphanages. Precisely because of the country pay attention and protect the rights of the child and must be upheld by any person; However, in practice the law enforcement issues (law enforcement) often experience obstacles and constraints caused by internal and external factors, the system crime sometimes still treat children involved as perpetrators of the crime as perpetrators of criminal acts committed by adults. The child is placed in a position as a criminal who deserves to get the same punishment as adults and apply in Indonesia, should be oriented to the individual offender or commonly called the accountability of individual / personal (Individual responsibility), the offender was seen as individuals who are able to take full responsibility for the act of doing. While the child is an individual who has not been able to fully realize the actions / deeds he does, it is because the child is an individual who is immature thinking. Without realizing it of course can lead to severe psychological impact on the child that ultimately affect the mental development and the soul of the child, it is concerned that the child quickly imitate the treatment of people who are nearby. One of the main properties of delinquency (called Juvenile Deliquency), is an act or acts of violation of norms, both legal norms and social norms committed by children younger ages. Conditions delinquency or known child delinquency is defined as a form of crime by children under title-specific title of the section of the Criminal Code and / or governance legislation. While the juvenile court was formed because the background of concern over the attitude of the actions undertaken criminalization of children and youth who number from year to year increase. But the treatment of adult criminals, requiring special protection measures for the perpetrators of the children; Juvenile court is intended to cope with unfavorable circumstances for children, and in the execution of juvenile criminal justice process should not be treated the same as adults. Indonesia's judiciary really consider the interests of children need to be realized to ensure the interests of children through Law Number 11 Year 2012 on Openness Child Criminal Justice; In order to overcome the problems of criminal offense committed by children, all of them shall be tried in court for a child who is on trial in the general court; The law gives national legal basis for legal protection for children through the juvenile justice order. Additionally intended as legal devices more robust and adequate to implement guidance and providing legal protection for children in conflict with the law and the enforcement of legal rights and child to embody the principle of the best interests of the child (the best interest of the child). In the act of deprivation of liberty, for example, should be done only as a measure of last resort, where the case concerning the right of children not to be separated from their parents. Kids as immature individuals need to obtain legal protection / juridical (legal protection) in order to ensure their interests as members of the public, enforcement issues and legal rights of children, basically the same as the overall law enforcement issues. Therefore, law enforcement issues of children affected by several factors, among others: 1. For law enforcement officers or relating to the legal process in society in Indonesia, officers responsible for enforcing the law known as the chess dynasty including the police (the investigating agency), prosecutor (prosecutor), the judge (judicial), and attorney or advocate. To deal with common problems in Indonesia, namely the limited ability of the law enforcement agencies who understand the law and the rights of children, the quality of, education and expertise of each apparatus, as well as the organization's ability to enforce the law and the rights of the child. 2. The legal culture of society, the social structure and cultural outlook of ongoing and people believed in enforcing the law as a guide everyday behavior. is an important issue in enforcing the law in Indonesia because it involves public confidence in the legal and law enforcement authorities; Equally important to the legal community, which is where the movement of law in everyday life that include the extent to which compliance with the law society, caring for enforcing the law towards order and peace. While the child is only a guideline legal precedent to guide how people act when the child's problems are found. According to Law No. 11 of 2012 on the Criminal Justice System Children in Article 69 paragraph (2) Children who are no older than 14 (fourteen) years may be subject only. The offense can be imposed on offenders Kids are: (1) Capital punishment for children consists of: a. Criminal warning; b. criminal terms: 1) development outside the institution; 2) community service; or 3) supervision. c. Work training; d. Coaching in the institution; and e. Jail. (2) Criminal additional consisting of: a. appropriation of profits derived from the crime; or b. fulfillment of customary obligation. (3) If the material law punishable cumulative prison term and a fine, penalty replaced with job training (4) The penalties meted out to children not violate the dignity of the Child. Differentiation penalty of children is determined by the Code of Penal (Penal Code), in the imposition of a maximum determined punishment ½ of the maximum threat to adults, while the imposition of the death penalty and life imprisonment shall not apply to children. Sanctions imposed against children in this law is determined by age, which is for children aged 12 to 15 years only subject to the action, while children who were aged 12 to 18 years will be punished; To create a harmony and balance within the community held sanction. Sanctions are formed of a system or an institution authorized to take; The purpose of reaction to crime and delinquency is for the prevention of crime and delinquency, and criminal actor resocialization. Criminal system prevailing today in Indonesia only depends on the nature punishment without regard to how it can change the child gets better, for example just given criminal system that is instructive, that is a criminal system that not only emphasizes the terms punishment, but how a child behavior that can be changed for the better and will not repeat the action without having sanctioned entity or prison. In-Law No. 35 of 2014 on Child Protection in Article 17 paragraph (1) every child deprived of liberty shall: a. get treated humanely and placing separated from adults. b. Legal aid or other assistance effectively in every stage applicable legal remedies, such as social assistance from social work, consultations of psychologists and psychiatrists or assistance from linguists. c. Defensively and justice in front of the juvenile justice objectively and impartially in a trial closed to the public. Perpetrators of crimes committed by children would be easier to control and improvement than adults, and this is because the level of the child's development was in contrast to the properties and characteristics, in infancy, young adults and the elderly will be different psychologically and physically ; Medium criminal system by providing criminal sanctions is instructive / educational been rarely carried out by law enforcement officials in Indonesia. One example is instructive criminal sanctions are criminal sanctions are not only returned to a parent / guardian or the environment, but the nature of criminal sanctions, for example educate put religious institutions in accordance with the religious / her faith. While the criminal system of individual (individual responsibility) is used for this is the response to crime that is fragmented only see prevention in terms of individual / personal, even though in dealing with the problem of children not only seen from the response the individual child alone, but viewed from many factors , one of them how the child is no longer repeat his actions, but provides a good example and education to the child itself; It is intended that the child's mental and spiritual well-educated, so that the misbehavior of the child for the better. With the inclusion of the child as the perpetrators of crimes to the Penitentiary instead does not guarantee that the child can be changed, otherwise not be both mental and spiritual children because they were exiled together with the perpetrators of criminal acts of others this has resulted in the recovery of the child's behavior to be more good hampered due to the environment itself unfavorable. Surely it would be different if placing the child in an environment that does not feel treated as a criminal, but rather to treat the child as an immature man who still do not know anything so they need to be given guidance of education is called positive action and good. Of course, the treatment given to those involved in criminal acts, as long as the legal process and punishment put them as young criminals who have different characteristics with adult criminals. Actually the criminal system that is instructive as this is not something new, because in law juvenile justice system, the system punishment didactic had clearly expressed therein, but this is rarely done, even less children are dealt enforcement laws that have not been professionally handle cases of children, sometimes the placement of children mixed with adult convicted; There are two alternative actions that can be taken if the crime committed by children before even the age of 18 (eighteen) years and filed through reaching the age limit of 21 (twentyone) years old, the child remains a child brought to trial. Average child who has not aged twelve (12) years of committing or suspected of committing a crime, then the Investigator, Supervisor of Community and Professional Social Workers take a decision that is first hand it back to parents, guardians / foster parents, if the child can still be fostered , Second, include it in educational programs, coaching, and mentoring in government agencies in charge of social welfare, both at national and regional levels, not later than 6 (six) months; But pay attention to the child's interests, the judge may require handed over to social organizations.